AN ANALYSIS OF USING MOVIE LOST IN TRANSLATION IN SOCIOLINGUISTICS CLASS ON THE SEVENTH SEMESTER STUDENTS UNDERSTANDING CULTURE AND LANGUAGE - Sigit - Rinaldi; Nargis - -; Eka Ugi Sutikno; Yudhie Indra Gunawan; Moh Iqbal Firdaus (Globish: An English-Indonesian Journal for English, Education, and Culture, 2023)
This study aims to determine whether using the Lost In Translation film media can improve student understanding in  culture and language in the sociolinguistic class and how a film with the title Lost In Translation can affect student understanding. This study uses a qualitative approach in a descriptive analytical model. The instruments or tools used by researchers in collecting data were questionnaires and documents. a questionnaire (list of statements) containing 20 statements with a Likert scale which  results will be described descriptively, in taking the assessment the researcher calculates the results of the questionnaire which is a seventh semester student of sociolinguistics class content and documents in the form of photos of several film scenes showing the existence of several cultures and languages this movie. The results of the study have shown the final score of 2158 with an average grade  of 120 which indicates that students agree that the Lost In Translation film media can affect students' understanding  and knowing the language culture in the seventh semester sociolinguistics class of the Faculty of Education and Education at Muhammadiyah University of Tangerang.